MINDFUL TEACHING AND LEARNING: A SYSTEMATIC REVIEW OF MODELS, STRATEGIES, AND OUTCOMES IN EDUCATIONAL CONTEXTS - Muhammad Abduh (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This systematic literature review examines how mindfulness has been implemented in teaching and learning across educational settings from 2010 to 2024. Forty peer-reviewed studies were identified through Scopus and Web of Science, and analyzed thematically using NVivo 14 Plus. The review highlights six dominant models, Mindfulness-Based Stress Reduction (MBSR), Langerian mindfulness, trauma-informed care (TIC), culturally responsive practices (CRP), social and emotional learning (SEL), and contemplative pedagogy. Implementation strategies include direct mindfulness exercises, curriculum integration, and professional development for teachers. Across studies, mindfulness fosters academic improvement, emotional regulation, empathy, and classroom harmony, while reducing stress and behavioral problems. Teacher mindfulness practice enhances instructional quality and relational climate. Overall, mindfulness emerges as a transformative pedagogical orientation that integrates equity, compassion, and well-being, emphasizing the need for sustained and culturally grounded implementation education. Future research should emphasize longitudinal and culturally grounded, and systemic approaches to support sustainable mindfulness integration across diverse educational settings.